IMPACT OF FEEDING VARIED QUANTITY OF “TUKRA” INFECTED MULBERRY LEAVES ON THE ECONOMIC CHARACTERS OF MULTI VOLTINE SILKWORM BOMBYX MORI L. - VINUTHA, K.; ARUNA, A.S.; PRASAD, K. SATHYA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
The studies on the impact of feeding different proportion of tukra affected and healthy mulberry leaves on the rearing performance of polyvoltine x bivoltine silkworm Bombyx mori hybrid were carried out and the results indicated a significant increase in larval and cocoon and pupal weight which varied with the treatments. No significant variation ¡n other quality parameters like shell percent, larval duration, single filament length, renditta, denier was observed. The feeding extent of tukra infested leaves for silkworm rearing was discussed.